2018
DOI: 10.7759/cureus.2857
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Percutaneous Intervention of a Left Main Coronary Artery Stenosis Without the Use of Intravascular Imaging

Abstract: ObjectivesThe aim of this study was to assess the prognosis in patients with left main coronary artery stenosis one year after percutaneous coronary intervention (PCI).MethodsOur study included 40 patients who underwent PCI for left main coronary artery stenosis without the use of intravascular ultrasound (IVUS). Patients were followed for a year, and the prognostic effect of PCI on a composite end-point of revascularization, new myocardial infarction, cardiac death, and on all-cause mortality was assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…We found an increased risk of MACCE in patients with LMCA disease in older age, diabetics, and with a history of MI, low EF, and high SYNTAX score. In a study by Mahmoud and colleagues, they found that diabetes, smoking, body mass index, hypertension, the complexity of the vessel, and ejection fraction were predictors of MACCE after PCI for LMCA disease [17] . The SYNTAX score was a predictor of mortality and MACCE in patients with PCI for LMCA disease [18] .…”
Section: Discussionmentioning
confidence: 99%
“…We found an increased risk of MACCE in patients with LMCA disease in older age, diabetics, and with a history of MI, low EF, and high SYNTAX score. In a study by Mahmoud and colleagues, they found that diabetes, smoking, body mass index, hypertension, the complexity of the vessel, and ejection fraction were predictors of MACCE after PCI for LMCA disease [17] . The SYNTAX score was a predictor of mortality and MACCE in patients with PCI for LMCA disease [18] .…”
Section: Discussionmentioning
confidence: 99%